Adaptación y validez del cuestionario de comportamiento sexual seguro (ssbq) para población migrante - Guerra Ordoñez, Jesús Alejandro; Benavides Torres, Raquel Alicia; Zapata Garibay, Rogelio; Salazar Barajas, Martha Elba (NOVA, 2020)
The US-Mexico border has received large migratory groups from the center and south of the country, as well as from Central American countries. Migra.nts are considered a vulnerable group to HIV acquisition as they r~p?rt ~lg~ rates of high-risk sexual behavior. It is necessary to have empirical indicators specialized in this population and adapted to its cultural context that allows us to know important aspects of its behavior such as sexual nature. This work aimed is to test the reliability and validity of the ~afer Sex Behavior Questionnaire (SSBQ) adapted for the migrant populat.lOn. We use focal groups and a sample of 311 migrants for the adap.tatlOn translation and back-translation of the questionnaire. The modified q~estionnaire presented a Cronbach's Alpha of 0.76, the KaiserMeyer-Olkin (KMO) sample adequacy = 0.738, Bartlett's sphericity test (X2 ': 1635.5.44; gl = 276, P < 0.000), and factor analysis with varimax rotauon for .flve factors resulted in good sc<?resand explained 46.97% of the to.tal va.flance. Therefore, it can be concluded that the adaptation of the questionnaire for the migrant population is valid and reliable.